Emerging Trends in Distribution in the Life Insurance Sector in India: A Study of a few Leading Players - Sinha, Abhijit (Indian Journal of Marketing, 2013)
The life insurance industry in India had its birth in the early part of the nineteenth century. For better management of the insurance business, several Acts have been passed from time to time. Two noteworthy events in the history of life insurance are (i) the formation of the Life Insurance Corporation of India in 1956, which served as a monopoly till the year 2000 followed by (ii) the opening up of the insurance sector to the private players in 1999, who were given the permission to operate either single-handedly or as a joint venture with any other private player(s) and/or foreign partner. This drastic regulatory change brought an end to the monopoly status of LIC, and also encouraged the private players to enter into the insurance space. To keep pace with the fast-changing industry environment, one of the functions that is gaining strategic importance is the coming up of newer channels of distribution, which would spread the business to newer markets and serve the customers cost-effectively, steadily, and speedily. This exploratory research (which was carried out in the time period from May-July 2012) discusses the various distribution channels (that emerged in the deregulated period and changed the overall industry trend) operating over a period from 2005-06 to 2009-10. The researcher considered seven dominating private players in the life insurance industry to understand the recent patterns in distribution. The analysis clearly shows a move-away from the traditional channels by the private sector.